2020
DOI: 10.1097/ta.0000000000002946
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric adjusted reverse shock index multiplied by Glasgow Coma Scale as a prospective predictor for mortality in pediatric trauma

Abstract: INTRODUCTION Shock index and its pediatric adjusted derivative (pediatric age-adjusted shock index [SIPA]) have demonstrated utility as prospective predictors of mortality in adult and pediatric trauma populations. Although basic vital signs provide promise as triage tools, factors such as neurologic status on arrival have profound implications for trauma-related outcomes. Recently, the reverse shock index multiplied by Glasgow Coma Scale (GCS) score (rSIG) has been validated in adult trauma as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…To contrast this, penetrating injury has recently been demonstrated in more than 40% of pediatric injuries within combat environments, suggesting that the injury patterns between these studies are not comparable. 16,17 Furthermore, the rSIG cutoff values that we previously demonstrated from combat-related data were relatively higher than the values seen within this study. For instance, this study demonstrated optimal cutoff values of 5.2, 5.9, 9.0, and 9.6 for children aged 0 to 3, 4 to 6, 7 to 12, and 13 to 18 years, respectively.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…To contrast this, penetrating injury has recently been demonstrated in more than 40% of pediatric injuries within combat environments, suggesting that the injury patterns between these studies are not comparable. 16,17 Furthermore, the rSIG cutoff values that we previously demonstrated from combat-related data were relatively higher than the values seen within this study. For instance, this study demonstrated optimal cutoff values of 5.2, 5.9, 9.0, and 9.6 for children aged 0 to 3, 4 to 6, 7 to 12, and 13 to 18 years, respectively.…”
Section: Discussioncontrasting
confidence: 77%
“…To contrast this, our previous work using military data found the optimal cutoff values of 8.3, 10.5, and 10.8 for children aged 0 to 6 years, 7 to 12 years, and 13 to 18 years, respectively. 17 We believe that this may be due to several reasons. While the differing patient populations and associated injury patterns likely accounts for some of the variation, the mortality rates displayed in our previous work were largely only representational of early death within the resuscitative phase because of the circumstances often surrounding the medical rules of engagement in combat zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed uses include intensive care unit admission guidelines, 17,18 study inclusion criteria, 25 and risk prediction 21 . It has also been incorporated as one component of multifaceted mortality prediction tools 16,21,26 …”
mentioning
confidence: 99%
“…[8][9][10] Reverse shock index multiplied by Glasgow Coma Scale has recently been shown to be more predictive of mortality than SIPA in both military and civilian settings. 11,12 This suggests that rSIG may be more generalizable than SIPA to pediatric trauma patients regardless of injury mechanism; however, its full utility is unstudied in the pediatric population. Thus, the purpose of this study was to determine if rSIG is a useful tool for identifying severely injured pediatric trauma patients.…”
mentioning
confidence: 99%